Integrating Ethnopedagogy-Based E-Learning to Enhance Creativity of Prospective Elementary School Teachers: Student and Lecturer Perceptions - Muhammad Erfan; Ni Made Yeni Suranti; Ibrahim; Siti Istiningsih; Nurul Kemala Dewi (Postgraduate, University of Mataram, 2025)
In the digital era, integrating local cultural knowledge through ethnopedagogy makes science learning more contextual and engaging. This study examines the practicality of an ethnopedagogy-based e-learning tool for prospective elementary school teachers using the develop phase of the 4-D model. Practicality was assessed through classroom observations and questionnaires administered to both lecturers and students. Observation showed excellent implementation (average score 99.67%). Lecturers’ responses using a 1–5 Likert scale also showed high averages: 4.57 for the Semester Learning Plan, 4.64 for the Student Assignment Plan, 4.41 for the Student Worksheet, 4.35 for Teaching Materials, and 4.55 for the e-learning aspect. Student responses further confirmed the tool’s practicality, with scores of 4.35 for understanding ethnopedagogy, 4.75 for LMS engagement, 4.80 for ease of access and use, 4.46 for facilitating creativity, 4.85 for feedback and evaluation, and 5.00 for learning quality. The use of structured questionnaires provided comprehensive insights into the tool’s usability, cultural relevance, and effectiveness in facilitating interactive learning. Although minor loading issues occurred, they did not hinder learning. These findings indicate that the ethnopedagogy-based e-learning tool is highly practical and supports effective, culturally responsive science education at the elementary level.